2016
DOI: 10.4167/jbv.2016.46.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Indirect ELISA for Detection of Antibodies to Getah Virus in Horse Serum

Abstract: Getah virus (GETV) is a member of the genus Alphavirus in the family Togaviridae. GETV infection can occur in a wide range of vertebrate species, and the virus has been known for a pathogen of horses and pigs. To rapidly and accurately diagnose GETV infection of a racehorse, an indirect ELISA (I-ELISA) was developed in the present study for detection of antibodies to GETV in serum samples. To evaluate the developed I-ELISA, a total of 240 serum samples from Thoroughbred racehorses raised in Korea were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Even so, there is still no efficient commercial diagnostic kit for GETV antibodies, leading to serious inconvenience to both carry out epidemiological investigation of GETV disease and further strengthen the prevention and control of GETV disease. Taking ELISA’s advantages of sensitivity and suitability for the detection of large quantities of samples, some studies have reported that ELISA methods for detecting GETV antibody derived from pigs and horses could be established successfully using purified GETV virion as antigens ( Lee et al, 2016 ). However, this method of preparing antigens utilizing virion may face the bio-safety risk of virus dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, there is still no efficient commercial diagnostic kit for GETV antibodies, leading to serious inconvenience to both carry out epidemiological investigation of GETV disease and further strengthen the prevention and control of GETV disease. Taking ELISA’s advantages of sensitivity and suitability for the detection of large quantities of samples, some studies have reported that ELISA methods for detecting GETV antibody derived from pigs and horses could be established successfully using purified GETV virion as antigens ( Lee et al, 2016 ). However, this method of preparing antigens utilizing virion may face the bio-safety risk of virus dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we purified GETV using the sucrose gradient method and reported an I-ELISA with sensitivity (86.3%) and high specificity (94.5%) compared with that of the VN test (16). In this study, we developed a blocking ELISA (B-ELISA) with high sensitivity and specificity that can be applied to several animal species because GETV transmitted by mosquitoes can cause disease in several animals.…”
Section: Introductionmentioning
confidence: 99%